Uric acid deposits and estivation in the invasive apple-snail, Pomacea canaliculata - Giraud Billoud, Maximiliano German (2011)
The physiological ability to estivate is relevant for the maintenance of population size in the invasive Pomacea canaliculata. However, tissue reoxygenation during arousal from estivation poses the problem of acute oxidative stress. Uric acid is a potent antioxidant in several systems and it is stored in specialized tissues of P.canaliculata. Changes in tissue concentration of thiobarbituric acid reactive substances (TBARS), uric acid and allantoin were measured during estivation and arousal in P. canaliculata. Both TBARS and uric acid increased two-fold during 45 days estivation, probably as a consequence of concomitant oxyradical production during uric acid synthesis by xanthine oxidase. However, after arousal was induced, uric acid and TBARS dropped to or near baseline levels within 20 min and remained low up to 24 h after arousal induction, while the urate oxidation product allantoin continuously rose to a maximum at 24 h after induction, indicating the participation of uric acid as an antioxidant during reoxygenation. Neither uric acid nor allantoin was detected in the excreta during this 24 h period. Urate oxidase activity was also found in organs of active snails, but activity shut down during estivation and only a partial and sustained recovery was observed in the midgut gland.